Formal faculty observation and assessment of bedside skills for 3rd-year neurology clerks. (22nd November 2016) - Thompson Stone, Robert; Mooney, Christopher; Wexler, Erika; Mink, Jonathan; Post, Jennifer; Jozefowicz, Ralph F.
Abstract : Objective: To evaluate the feasibility and utility of instituting a formalized bedside skills evaluation (BSE) for 3rd-year medical students on the neurology clerkship. Methods: A neurologic BSE was developed for 3rd - year neurology clerks at the University of Rochester for the 2012–2014 academic years. Faculty directly observed 189 students completing a full history and neurologic examination on real inpatients. Mock grades were calculated utilizing the BSE in the final grade, and number of students with a grade difference was determined when compared to true grade. Correlation was explored between the BSE and clinical scores, National Board of Medical Examiners (NBME) scores, case complexity, and true final grades. A survey was administered to students to assess their clinical skills exposure and the usefulness of the BSE. Results: Faculty completed and submitted a BSE form for 88.3% of students. There was a mock final grade change for 13.2% of students. Correlation coefficients between BSE score and clinical score/NBME score were 0.36 and 0.35, respectively. A statistically significant effect of BSE was found on final clerkship grade ( F 2, 186 = 31.9, p < 0.0001). There was no statistical difference between BSE score and differing case complexities. Conclusions: Incorporating a formal faculty-observed BSE into the 3rd year neurology clerkship was feasible. Low correlation between BSE score and other evaluations indicated a unique measurement to contribute to student grade. Using real patients with differing case complexity did not alter the grade.